Education Across the African Diaspora, 1500–2020. Issue 2 (15th March 2021) - Manning, Patrick
ABSTRACT: Education in the African Diaspora unfolded under difficult conditions yet provided its communities with individual advancement, conceptual discoveries, and institutional achievements. Examining regions across the of African Diaspora, this essay explores education in the era of enslavement and emancipation (up to 1880); in times of industrialization and segregation (up to 1950); and the era of decolonization, civil rights, and high-level educational achievement up to the present. The concept of the African Diaspora is shown to be a major accomplishment of these educational interactions.